Vnos tujerodnih organizmov v severnem Jadranu in upravljanje balastnih vod - David, Matej (Annales. Series historia naturalis, 1999)
The article calls our attention to the existing dangers of nonindigenous organisms being introduced in our sea with ballast water and to the need to have this matter strictly under control. Some plankton investigations have proved that various types of bacteria as well as plant and animal species can survive in ballast water and sediment even after a journey lasting for a few months. The ballast water, filled on one side of the world and emptied on the other, can contain some hramful nonindigenous organisms. Although only a minor research of this kind has been carried out in Slovenia ...
Keywords: balastne vode; management; severni Jadran; tujerodne vrste; upravljanje